2019
DOI: 10.3390/cells8080893
|View full text |Cite
|
Sign up to set email alerts
|

PML Bodies in Mitosis

Abstract: Promyelocytic leukemia (PML) bodies are dynamic intracellular structures that recruit and release a variety of different proteins in response to stress, virus infection, DNA damage and cell cycle progression. While PML bodies primarily are regarded as nuclear compartments, they are forced to travel to the cytoplasm each time a cell divides, due to breakdown of the nuclear membrane at entry into mitosis and subsequent nuclear exclusion of nuclear material at exit from mitosis. Here we review the biochemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 146 publications
0
20
0
Order By: Relevance
“…ICP0 was initially identified as an E3 Ub ligase by virtue of its ability to localize to and disrupt PML-NBs ( Everett, 2000 ; Maul et al, 1993 ; Maul and Everett, 1994 ; Everett and Maul, 1994 ; Everett et al, 1998 ; Chelbi-Alix and de The, 1999 ). PML-NBs are highly dynamic nuclear substructures composed of more than 70 proteins that respond to a variety of stimuli, including heat shock, cytokine signalling, and virus infection ( Lang et al, 2010 ; Van Damme et al, 2010 ; Hoischen et al, 2018 ; Lang et al, 2019 ; Bernardi and Pandolfi, 2007 ; Maul et al, 1995 ). Infecting HSV-1 genomes are rapidly entrapped by PML-NBs upon nuclear entry ( Alandijany et al, 2018 ; Dembowski and Deluca, 2017 ), a host response that can lead to viral genome silencing as a component of the intrinsic antiviral immune response (discussed below) ( Alandijany et al, 2018 ; Everett et al, 2006 ; Everett et al, 2008a ; Glass and Everett, 2013 ; Cabral et al, 2018 ).…”
Section: Icp0-mediated Degradation Of Pml-nbs and Sumoylated Host Promentioning
confidence: 99%
“…ICP0 was initially identified as an E3 Ub ligase by virtue of its ability to localize to and disrupt PML-NBs ( Everett, 2000 ; Maul et al, 1993 ; Maul and Everett, 1994 ; Everett and Maul, 1994 ; Everett et al, 1998 ; Chelbi-Alix and de The, 1999 ). PML-NBs are highly dynamic nuclear substructures composed of more than 70 proteins that respond to a variety of stimuli, including heat shock, cytokine signalling, and virus infection ( Lang et al, 2010 ; Van Damme et al, 2010 ; Hoischen et al, 2018 ; Lang et al, 2019 ; Bernardi and Pandolfi, 2007 ; Maul et al, 1995 ). Infecting HSV-1 genomes are rapidly entrapped by PML-NBs upon nuclear entry ( Alandijany et al, 2018 ; Dembowski and Deluca, 2017 ), a host response that can lead to viral genome silencing as a component of the intrinsic antiviral immune response (discussed below) ( Alandijany et al, 2018 ; Everett et al, 2006 ; Everett et al, 2008a ; Glass and Everett, 2013 ; Cabral et al, 2018 ).…”
Section: Icp0-mediated Degradation Of Pml-nbs and Sumoylated Host Promentioning
confidence: 99%
“…Conversely, no co-staining at condensed chromatin was observed between PML and IE1 mutants highly defective in PML body targeting (IE1cc134-136, cc161-165, cc172-176, cc258-263, cc286-292, cc307-310, cc318-319). In the presence of these IE1 mutants, or in the absence of IE1 proteins, PML formed complexes referred to as MAPPs across the mitotic cells (reviewed in [96,97]). These complexes were also observed in cells expressing IE2, but not when wild-type IE1 was expressed.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The human-and primate-specific L1 ASPs reportedly drive ORF0-containing transcripts, whose encoded protein, ORF0p, is predominantly nuclear and localizes in close proximity to PML-NBs 12 . PML-NBs are implicated in various biological processes, including mitosis 27 . Because our cell cycle analysis demonstrated that L1 ASP activation shortens the duration of the S-G2 phase, L1 ASP activation may accelerate mitosis through PML-NBs and L1 ASP-driven ORF0p, thereby supporting efficient cell growth.…”
Section: Discussionmentioning
confidence: 99%